(untitled) (Aporte Santiaguino, 2023)
The objective of the work is to implement a Management system for the use of construction and demolition waste (RCD) from public and private works. The information used is the works carried out in the urban area of ​​the Independencia district in the period 2010 to 2015 (91 works by contract modality and 34 by direct administration) that contains: Name of the work, SNIP code, start date and Completion of the work and budgeted activity related to RCD: removal of surpluses, demolition of concrete structures, demolition of asphalt pavement, demolition of masonry, demolition of adobe construction, extraction of existing and total concrete pipes. The survey to determine the factors and degree of user acceptance, for the use of RCD, was validated by three experts and addressed to the general user public of the District of Independencia, and another for professional builders and engineers. The amount of RCD of the executed works is 197 618,60 m3 with a predominance of elimination of surplus material. According to the surveys carried out, the population assumes that the MDI "does not have" an RCD Management Instrument, regarding the final disposal, the reuse of the RCD is proposed.